2019
DOI: 10.1101/816025
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determining the association between regionalisation of cortical morphology and cognition in 10,145 children

Abstract: During development individuals undergo protracted changes in cortical morphology, which coincide with changes in cognition. A number of studies have measured the association between brain structure and cognition in children, however these frequently rely on mass univariate statistics or ROI-based comparisons and do not always measure cortical morphology relative to global brain measures. After controlling for global brain measures, we can see a residual regionalisation pattern indicating the size or thickness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Here, we found that including the covariance structure of the imaging phenotype during parameter estimation greatly improved the predictive performance of functional imaging phenotypes. Similar improvement of predictive accuracy of regional cortical morphology on cognitive outcomes was shown in children (Palmer et al 2020). Predictive performance is of great importance to the utility of biomarkers on clinical disorders or cognitive processes.…”
Section: Discussionsupporting
confidence: 70%
“…Here, we found that including the covariance structure of the imaging phenotype during parameter estimation greatly improved the predictive performance of functional imaging phenotypes. Similar improvement of predictive accuracy of regional cortical morphology on cognitive outcomes was shown in children (Palmer et al 2020). Predictive performance is of great importance to the utility of biomarkers on clinical disorders or cognitive processes.…”
Section: Discussionsupporting
confidence: 70%
“…Currently, brain-wide association studies are trapped in the initial discovery phase. Larger samples will inevitably allow multivariate models, both those currently in use and future improvements currently being developed [38][39][40][41] , to be employed by individual research groups. Smaller, investigator-initiated neuroimaging studies will continue to be just as important for human neuroscience as they were in the days when samples of N>10,000 for brainwidewide association studies (BWAS) were still an impossibility.…”
Section: Towards Reproducible Brain-wide Association Studies Through mentioning
confidence: 99%
“…In our previous study, we used a Bayesian polyvertex score (PVSB) to quantify the variance in each cognitive phenotype predicted by the vertex-wise imaging data for the regionalisation of CSA and CTH (see supplementary figure 3 for a summary of these findings 24 ). The PVSB represents a linear weighted sum of the vertex-wise associations, which are projected from a training set to an independent hold-out set within a cross validation framework.…”
Section: Partitioning the Variance Between Brain Structure And Cognitionmentioning
confidence: 99%
“…We recently demonstrated that there were significant associations between the regionalisation of CSA and CTH (when controlling for global structural measures) and the fluid and crystallised composite scores from the NIH Toolbox within the ABCD baseline sample using the Multivariate Omnibus Statistical Test: the MOSTest 24 . This test aggregates vertex-wise associations across the cortex thereby improving our power for detecting widely distributed effects compared to the standard neuroimaging approach [24][25][26] . Given the graded nature of the biology underlying the patterning of the cortex this is a more appropriate statistical approach compared to standard neuroimaging methods.…”
Section: Distinct Associations Between Cortical Morphology and Differmentioning
confidence: 99%
See 1 more Smart Citation